57 Can a structured intervention programme improve the biophysical and psychosocial wellbeing in children with congenital heart disease?. (28th September 2016) - Callaghan, S; Morrison, L; McCusker, C; Casey, FA
Abstract : Introduction: Improved survival among children with congenital heart disease (CHD) has shifted focus to the long-term physical and psychological outcomes for these patients. There is evidence that children with CHD have lower levels of daily physical activity and a higher prevalence of obesity compared to their normal peers. The benefits of an active lifestyle within the general population have been well described. They include better cardiovascular health, improved psychological, cognitive and social functioning and obesity prevention. This study aims to determine if a structured intervention programme can improve both physical and psychological functioning in children with CHD. Methods: This study is a prospective randomised control trial. 430 patients aged between 5–10 years with CHD were identified on Heartsuite Database and invited to participate. Each patient underwent baseline biophysical and psychological assessment as detailed below: Biophysical assessments: Weight, height, waist measurements Baseline heart rate, blood pressure, oxygen saturation Exercise stress test – Graded cycle ergometer protocol Actigraph accelerometer worn for 1 week 3 day food diary Psychosocial assessments: Brief Symptom Index: To profile general mental health of the parent Kidscreen27 Strengths and Difficulties Questionnaire Butler Self-image Profile Following baseline assessment patients were randomised into intervention and control groups. The intervention group were invited to attend a one day education session during which motivational interviewing techniques were used to deliver advice on diet, exercise and positive lifestyle choices. They also received an individual written exercise plan to take home and implement. The control group continued with their usual level of care. After 4 months all participants were invited back for reassessment. Baseline results: 163 patients were recruited, 100 were male (61.3%) with a mean age of 8.4 years (range 5.3–11.5) Patient subgroups: 18.4% acyanotic no intervention, 37.4% acyanotic repaired, 27.6% cyanotic corrected, 16.6% cyanotic palliated EST: EST duration mean 5.89 mins (SD 2.02), METs mean 9.79 (SD 1.79), mean Maximal predicted HR 81% (SD 7.8) Actigraph: Average time spent in MVPA (Moderate-Vigorous Physical Activity) 45 mins (SD −27.2) The 'cyanotic palliated' subgroup had significantly lower EST duration, maximal HR and oxygen saturations at peak exercise compared with the other 3 subgroups, as well as significantly lower levels of daily MVPA The 'cyanotic palliated' group also scored significantly lower on HrQOL subscale, physical wellbeing Conclusions: The baseline assessments suggest that overall physical and psychological wellbeing is well preserved in the majority of children aged 5–11 years with CHD. The follow up results and impact of the intervention will also be presented.